Occurrence of adult acquired flat foot among diabetic patients in Rawalpindi and Islamabad: a cross-sectional descriptive study - Annam Saba; Haniya Iqbal; Laiba Ghayour; Aliya Ashraf; Onaisa Farooq; Faiza Waheed; Ateeqa Younis; Madiha Ashfaq (Turkish Journal of Kinesiology, 2023)
Human foot is a biological masterpiece, which is strong enough to support the body weight and flexible enough to adjust to various surfaces. Foot postural deviation can alter the alignment of the entire body. The collapse of the medial longitudinal arch of the foot causes one of the most prevalent deformities i.e. flat foot. Diabetic patients are more prone to have flat foot due to degeneration of posterior tibial tendon over the course of their disease. The aim of this study was to determine the occurrence of adult acquired flat foot and assess the disability of flat foot among diabetic population in Rawalpindi and Islamabad, Pakistan. In this cross-sectional descriptive study, 384 diabetic patients aged 35-60 year were enrolled after obtaining informed consent. Non-probability convenience sampling technique was employed. The data was gathered by performing navicular drop test to determine the presence of flat foot, assessment of posterior tibial tendon dysfunction through single heel rise test and by using foot function index questionnaire to assess pain, disability and activity limitation. Based on results of the study, posterior tibial tendon dysfunction was observed to cause the appearance of low navicular height leading to flat foot in 58.33% of the population. Moreover, there is a moderate tendency of occurrence of flat foot among diabetic population in the absence of other risk factors such as hypertension, obesity, steroids use and previous foot trauma etc. With regard to the functionality measured by foot function index, it was implied that the functional status of the patient was reduced because of the pain, disability and activity restriction in the presence of flat foot.